Better income from pest and disease- free tomatoes - Parupalli, V.L. Bharathi; Md. Harun-Or-Rashid; Huq, Syed Mahmudul; Dutta, Nirmal Kumar; Iqbal Faruk; Manickam, Ravishankar; Syed Nurul Alam; Krupnik, Timothy J. (TAFSSA, 2024)
This guide offers a concise overview of the major pests and diseases affecting tomatoes, highlighting their symptoms, the damage they cause, and providing cultural and biological control strategies for effective management.